(untitled) (International Journal of Physiotherapy, 2025)
Background: Sport-related concussion (SRC) is both challenging and fascinating to treat. Little guidance exists regarding the methods used to educate patients and families in physical therapy (PT) for SRC. To address this, I crafted educational materials emphasizing the positives regarding recovery prospects, along with pragmatic positivity in word choice and demeanor, when working with injured athletes and their families. After discharge, I conducted semistructured interviews to explore their experiences and identify common themes, analyzing them through the lens of the Theory of Self-Efficacy (SE). Methods: Athletes and a parent/guardian, who met criteria, were interviewed remotely. A 5-step phenomenological hermeneutic method was used for thematic analysis, and reports relating to operationally defined SE characteristics were recorded. A SE questionnaire was also given at the time of the interviews. Results: SE scores were high among all participants, particularly the parents/guardians, who averaged 36 out of a maximum score of 40 on the New General Self-Efficacy Scale (NGSE). Student athletes averaged 33.25 on the same scale. SE principles were frequently reported among athlete participants, who averaged 3.5 out of 4 themes represented. They reported strong peer and provider influence via social persuasion and mastery experience over their improvement during the process. Parents reported far fewer self-efficacy elements, with an average of 1.5, and relied heavily on their own prior experiences and opinions. Conclusion: Although the positive materials used in this study were not mentioned, the importance of rapport building and trust was evident in the participants’ responses. The high SE levels contributed to participants’ successful rehabilitation experiences, and the specific comments they made were varied and rich for clinicians to review and consider when thinking of their own interactions with patients and their families.